Processing of Fish Sauce by Chemical Hydrolysis from Red Meat of Tuna (Thunnus albacares) - Komariah Tampubolon; Winarti Zahiruddin; Sukria Kartanamulia (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2007)
Dark muscle in Thunnus albacares is considered as waste from frozen loin tuna and canned tuna processing. This waste still actually can be utilized as fish sauce which has economical value. The objectives of this research was to study the fish sauce processing by using acid hydrolysis with dark muscle tuna as raw material. Research was conducted in two steps, where the first step done in order to learn the influence fish and HCl ratio toward the quality of fish sauce especially for protein content. The ratio of fish and HCl were varies by w/w comprise 2:1 (A1), 1:1 (A2) and 1:2 (A3). The protein content of hydrolyzed fish sauce reach from 4.41-9.65 %, NPN 0.68-1.51 g/100 g, free amino acid 63.14-120.19 mg/100 g, NaCl 9.06-13.61%; TVN 100.48-167.91 mg/100 g, TMA 11.29-14.87 mg/ 100 g, total TDS 20.65-23.45 % and color 9.289-0.693. Fish sauce (A1) considered as the best product, therefore in the later/pursued study in this ratio was used as primary treatment combined with various concentration of caramel 0 % (B1); 2.5 % (B2); 5 % (B3); 7.5 % (B4) and 10 % (B5). The addition of caramel tend to increase color intensity and stickiness of fish sauce. Panelist prefer to chose the commercial fish sauce, however the hydrolyzed fish sauce produced from this study still has higher protein content. Fish sauced was still also to liquid, the color still darker and the taste still strange.Key words: chemical hydrolisis, fish sauce, Thunnus albacares